AKAP95 interacts with nucleoporin TPR in mitosis and is important for the spindle assembly checkpoint. Issue 10 (19th May 2017) - López-Soop, Graciela; Rønningen, Torunn; Rogala, Agnieszka; Richartz, Nina; Blomhoff, Heidi Kiil; Thiede, Bernd; Collas, Philippe; Küntziger, Thomas
ABSTRACT: Faithful chromosome segregation during mitosis relies on a proofreading mechanism that monitors proper kinetochore-microtubule attachments. The spindle assembly checkpoint (SAC) is based on the concerted action of numerous components that maintain a repressive signal inhibiting transition into anaphase until all chromosomes are attached. Here we show that A-Kinase Anchoring Protein 95 (AKAP95) is necessary for proper SAC function. AKAP95-depleted HeLa cells show micronuclei formed from lagging chromosomes at mitosis. Using a BioID proximity-based proteomic screen, we identify the nuclear pore complex protein TPR as a novel AKAP95 binding partner. We show interaction between AKAP95 and TPR in mitosis, and an AKAP95-dependent enrichment of TPR in the spindle microtubule area in metaphase, then later in the spindle midzone area. AKAP95-depleted cells display faster prometaphase to anaphase transition, escape from nocodazole-induced mitotic arrest and show a partial delocalization from kinetochores of the SAC component MAD1. Our results demonstrate an involvement of AKAP95 in proper SAC function likely through its interaction with TPR.